2017
DOI: 10.4048/jbc.2017.20.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Prognostic Significance of Transducin-Like Enhancer of Split 1 Protein Expression in Invasive Breast Cancer

Abstract: PurposeTransducin-like enhancer of split 1 (TLE1) is a member of the TLE family of transcriptional co-repressors that control the transcription of a wide range of genes. We investigated the prognostic significance of TLE1 protein expression in breast cancers by using immunohistochemistry and explored the relationship of TLE1 with clinicopathological parameters.MethodsImmunohistochemistry was performed on 456 cases of breast cancer tiled on tissue microarrays. The relationship between TLE1 expression in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…In invasive breast cancer, TLE1 was shown to be significantly associated with the human epidermal growth factor receptor 2+ and triple-negative breast cancer subtypes. However, this study did not find a significant association between TLE1 expression and disease-free survival (DFS) or overall survival (OS) (32).…”
Section: Discussioncontrasting
confidence: 83%
“…In invasive breast cancer, TLE1 was shown to be significantly associated with the human epidermal growth factor receptor 2+ and triple-negative breast cancer subtypes. However, this study did not find a significant association between TLE1 expression and disease-free survival (DFS) or overall survival (OS) (32).…”
Section: Discussioncontrasting
confidence: 83%
“…1,[4][5][6][7][8]12 Additionally, TLE1 expression has recently been identified in invasive breast cancer with high expression significantly associated with HER2 positivity. 13 Furthermore, certain populations of normal cells are variably labeled by TLE1, including endothelium, mesothelium, perineurium, basal keratinocytes, and adipocytes. 7 Indeed, in the present study, TLE1 was noted to also highlight sebaceous glands and follicular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…A well-established recent characterization study of PBX1 identified its importance as a valuable prognostic biomarker in BC. Defining signatures in chromatin facilitators involved in cancer characterized some of the pioneer factors like the GATA family of proteins, TLE1 protein, and PBX1 as a valuable prognostic biomarker in BC [68][69][70]. With the advent of newer technologies in genomics and proteomics, novel ER-associated pioneer factors have been continuously identified.…”
Section: Therapeutic Significance Of Targeting Er-associated Pioneer mentioning
confidence: 99%